Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers ... - White, Simone; Anderson, Peter; Gower, Graeme; Byrne, Matt; Bennett, Maria; Quin, Alison; Darling, Anna (RMIT University, 2024)
The Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers two-year project has culminated in a unique interactive website (see www.yourstoryourjourney.net) that houses a number of learning and teaching tools, strategies and resources designed to support all those working to improve the educational success of Aboriginal and Torres Strait Islander students in schools, Australia’s First Nations peoples. It is intended to be used in teacher education programs (pre-service and in-service), by teachers and school leaders, and by Aboriginal and Torres Strait Islander communities. The resource has been created to help all educators form relationships and partnerships with local communities, parents and caregivers to achieve better educational outcomes for all Aboriginal and Torres Strait Islander students. The resource positions educators as powerful agents of change. The project began from the premise that school education has traditionally involved ways of thinking and learning ...